Defamatory Speech Acts on Social Media: A Forensic Pragmatics Analysis - Mu'aliyah Hi Asnawi Asnawi (Journal of Pragmatics Research, 2026)
This study aims to analyze defamatory speech acts on social media from a forensic pragmatics perspective using a documentation study method. The research is grounded in the growing number of cases involving utterances that damage the reputation of individuals or groups through digital platforms such as Instagram, Twitter/X, TikTok, and YouTube. The research data were obtained from digital documentation in the form of posts, comments, and screenshots, supported by scholarly literature and relevant legal decisions. The analysis was conducted by identifying types of speech acts (locutionary, illocutionary, perlocutionary), communication contexts, and reputational effects based on Austin and Searle’s speech act theory. The findings indicate that the most dominant forms of speech acts in defamation cases are illocutionary assertives (43.34%) and expressive acts (40%), typically manifested as accusations, insults, or insinuations that harm a person’s reputation. However, given the complex and multimodal nature of online discourse often infused with cultural implicatures, irony, and digital semiotics the classical speech act framework may not be sufficient to capture the full pragmatic meaning. Therefore, integrating complementary approaches such as the appraisal system, stance analysis, or multimodal pragmatics can provide a more nuanced understanding of evaluative positioning, affective stance, and meaning construction in social media interactions. The forensic pragmatics analysis also reveals that indirect speech acts often carry the same legal consequences as explicit utterances, depending on the context, speaker's intention, and public perception. Digital traces (screenshots, metadata, comments, and reposts) are shown to function as linguistic forensic evidence in legal proceedings. The study concludes that the forensic pragmatics approach is effective for analyzing defamatory utterances, as it enables the simultaneous assessment of linguistic, contextual, and legal dimensions. The study recommends collaboration among linguists, law enforcement, and policymakers in developing guidelines for addressing defamation cases on social media.